2023
DOI: 10.1002/cam4.5841
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and efficacy of TACE combined with lenvatinib plus PD‐1 inhibitor in the treatment of hepatocellular carcinoma with portal vein tumor thrombus based on immunological features

Abstract: Background Although the appearance of portal vein tumor thrombus (PVTT) is significantly associated with unfavorable prognosis, there is insufficient evidence to confirm the efficacy and safety of the triple combination of transarterial chemoembolization (TACE), lenvatinib, and programmed cell death‐1 (PD‐1) inhibitor for patients with hepatocellular carcinoma (HCC) and PVTT. Furthermore, it remains unclear which patient type can obtain the best survival benefit from this combination therapy. Methods The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The results suggested that T-T-C combination therapy resulted in an improved OS, PFS, ORR and DCR compared with T-T combination therapy. A study by Zou et al ( 52 ) included 160 patients with advanced liver cancer, all receiving TACE + lenvatinib with or without PD-1 inhibitors, and focused on patient outcomes. The results showed that the triple therapy significantly extended the median OS (23.5 vs. 18.3 months; P=0.0002) and PFS (7.5 vs. 4.3 months; P<0.0001) times compared with the double therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that T-T-C combination therapy resulted in an improved OS, PFS, ORR and DCR compared with T-T combination therapy. A study by Zou et al ( 52 ) included 160 patients with advanced liver cancer, all receiving TACE + lenvatinib with or without PD-1 inhibitors, and focused on patient outcomes. The results showed that the triple therapy significantly extended the median OS (23.5 vs. 18.3 months; P=0.0002) and PFS (7.5 vs. 4.3 months; P<0.0001) times compared with the double therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Furthermore, serum procalcitonin levels and inflammatory cytokines VEGF, interleukin (IL)-17, IL-6, and IFN-α were found to be predictive biomarkers for lenvatinib in combination with TACE and PD-1 inhibitors in advanced HCC with large-vessel invasion. 36 37 However, the clinical application of the above-reported biomarkers was limited by the biological samples collection, low cost-effectiveness, and the prediction accuracy remained to be further improved. Moreover, relative studies have shown that radiomics can serve as a non-invasive and easily available method to predict treatment response in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zou et al. illustrated that TACE combined lenvatinib and PD-1 inhibitors has more promising clinical outcomes and acceptable safety when compared with TACE plus lenvatinib in patients with HCC and PVTT ( 21 ).…”
Section: Introductionmentioning
confidence: 99%